F. Moreno-Fernández; I. Penadés-Martínez; C. Ureña-Tormo; "Gramática fundamental del español" - Héctor Álvarez Mella (Cuadernos AISPI, 2020)
Francisco Moreno-Fernández; Inmaculada Penadés-Martínez; Clara Ureña-Tormo; "Gramática fundamental del español", New York: Routledge, 2020, 221 pp. ISBN: 978-1-138-35961-1